(untitled) (CIPEEX, 2025)
This study aimed to investigate the implications of the Labor Reform (Law 13,467/17) on convictions for bad faith litigation in the context of Brazilian Labor Procedural Law. Given the need to modernize labor relations and reduce abusive litigation, the reform incorporated into the CLT provisions that were previously applied in a subsidiary manner by the Civil Procedure Code. Using an inductive-descriptive methodology, the study analyzed legislation and case law to assess the effectiveness of legislative changes. The results indicate a reduction in labor demands and a moderation in claims after the reform, suggesting that the changes may have discouraged dishonest procedural practices. The research concludes that the reform strengthened the legal framework against bad faith litigation and draws attention to the importance of continually monitoring the effects of these changes, proposing future studies that explore the application of the law in different contexts and among different groups of workers.